Food uses and nutritional applications of resistant starches - Pascoli Cereda, Marney [UNESP]; Andrade, Luan Alberto (Elsevier, 2022)
This chapter provides a critical analysis on “resistant starch,” with a focus on underground starchy crops of South American origin. As a caloric food, starch always represents an asset for human development. In the last decades, this advantage became a problem, with increasing obesity, even in low development countries, together with serious health problems. In this context, the increasing interest in resistant starch is explained as a tool to reduce obesity. The incomplete digestion of resistant starch reduces the energy released and mimics the physiological functions of dietary fibers with positive health effects. But human body’s response is not standardized, which reduces the benefits of resistant starches. Starch complexation accounts for part of the advances in the control of starch digestion, but with the necessity of more research. Phenolics present in underground starchy crops may facilitate diabetes control, which could enhance the value of these raw materials as nutraceutical foods.
Keywords: diabetes control; enzymes; glycemic peak; Health; nutraceutical food; starch complexation